Från bondson till folkmusikikon : Otto Andersson och formandet av "finlandssvensk folkmusik" - Nyqvist, Niklas (Åbo : Åbo akademis förlag = Åbo Akademi University Press, 2007)
Summary: From peasant son to folk music icon - Otto Andersson and the formation of "Swedish folk music in Finland".
Väitöskirja
S. [5]-6: Innehållsförteckning. - S. 244-274: Källor och litteratur. - S. 275-286: Personregister.
Julkaistu myös verkkoaineistona.
Keywords: Andersson, Otto, -- 1879-1969.; Folk music -- Finland -- History and criticism; Musicologists -- Finland -- Biography; Musicology -- Finland -- History -- 20th century; Swedes -- Finland -- Music -- History and criticism; kansanmusiikki; musiikinhistoria; musiikintutkimus; oppihistoria; perinteenkerääjät; suomenruotsalaiset; tutkijat; tutkimushistoria; finlandssvenskar; lärdomshistoria; musikforskning; Suomi; väitöskirjat